The Explosive Crack Propagation Mechanism of Layered Rock Mass - Jinjing Zuo; Liwei Ma (Shock and Vibration)
Layered joints significantly affect the propagation and attenuation of engineering blasting stress waves and have a significant influence on rock breakage. In this study, the explosion crack propagation mechanism of a stratified rock mass with weak or no cementation is analyzed. Multilayer plexiglass plates are employed to simulate a layered rock mass, establishing an experimental model to investigate the vertical interaction between explosive charges and layered rock masses. The extent of ruptures and damage within the charging and sealing sections of the rock mass is analyzed. The explosion cracks at the bottom of the hole are relatively dense, whereas those at the hole opening are relatively sparse. The range of the crushing and fracture zones around the gun hole in the charging section is larger than that in the blocking section. Moreover, as the blocking section approaches the free plane, the crushing zone size decreases. A notable area of rapid damage escalation is identified between the blocking and charging sections, leading to a significant increase in damage intensity. The numerical analysis results indicate that the cumulative explosive energy within the charging section surpasses that of the blocking section, and the rate of energy accumulation is notably higher in the charging region.